Efficacy of different concentrations of saluyot (Corchorus olitorius L.) leaves extract as an antimicrobial agent against streptococcus mutans an in vitro study - Regine Angelique T. Carandang; Luneta, Criselda P. (Department of Community Dentistry, University of the Philippines Manila, 2015)
INTRODUCTION: Herbal remedies are commonplace in the Philippines, where a huge part of the population cannot afford conventional healthcare methods and this necessitates making use of natural resources to treat various ailments. Corchorus olitorius L., locally known as saluyot, has been found to aid in treating live disorders, gastrointestinal complications, and skin diseases. The present study examined if extract of saluyot leaves can inhibit the growth of Streptococcus mutans, the oral microflora most associated with dental caries, at different concentrations.